2018
DOI: 10.1371/journal.pone.0210019
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Clinical Index of Stable Febrile Neutropenia (CISNE) model in febrile neutropenia patients visiting the emergency department. Can it guide emergency physicians to a reasonable decision on outpatient vs. inpatient treatment?

Abstract: Advances in oncology have enabled physicians to treat low-risk febrile neutropenia (FN) in outpatient settings. This study was aimed to explore the usefulness of the CISNE model and identify better triage in the emergency setting. This is a retrospective cohort study on 400 adult FN patients presenting to the Emergency Department of National Cancer Center, Korea from January 2010 to December 2016. All had been treated with cytotoxic chemotherapy for solid tumors in the previous 30 days. The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
1
7
3
Order By: Relevance
“…Two previous studies have analyzed the performance of CISNE scores in patients with solid malignancies. Research by Koppaka et al [11] also showed that CISNE scores had an AUROC of 0.846, whereas in Moon et al [7], CISNE scores had an AUROC of only 0.66. In our study, the population of solid malignancies was dominated by headneck malignancies, whereas previous studies showed head-neck malignancies in only 5% of populations.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Two previous studies have analyzed the performance of CISNE scores in patients with solid malignancies. Research by Koppaka et al [11] also showed that CISNE scores had an AUROC of 0.846, whereas in Moon et al [7], CISNE scores had an AUROC of only 0.66. In our study, the population of solid malignancies was dominated by headneck malignancies, whereas previous studies showed head-neck malignancies in only 5% of populations.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the types of solid tumor in this study differed from the types of solid tumor in previous studies. In a study by Bayonas et al [2] and Moon et al, [7] the majority of solid tumor were breast cancer.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Various tools are available for risk stratification in adult patients with neutropenic fever, including the Clinical Index of Stable Febrile Neutropenia score, the Multinational Association for Supportive Care in Cancer risk index, and Infectious Diseases Society of America Risk Criteria. 4 However, there is currently no pediatric scoring tool to identify low-risk patients amenable to outpatient management, leading to significant variation in local practice patterns. 5 Although these findings suggest no difference in outcomes for inpatient versus outpatient treatment of low-risk patients, identifying optimal candidates for outpatient management is necessary.…”
Section: Commentarymentioning
confidence: 99%